SCREENING AND IDENTIFICATION OF LIPASE PRODUCING BACTERIA FROM DOMESTIC WASTEWATER - GARODE AM; SONUNE NA (International Journal of Pharma and Bio Sciences, 2014)
The ability of lipases is to perform very specific chemical transformation and it has made them increasingly popular in the food, detergent, cosmetic, organic synthesis, and pharmaceutical industries. The domestic wastewater is one of the good sources for isolation of lipase producing microorganism. Total 40 isolates were isolated from waste water on nutrient agar medium. All were screened for lipase activity on Tributyrin agar (TBA). Out of these, 10 bacterial isolates showed lipase activity. Out of these four isolates were found as maximum lipase producer. The isolate showing maximum activity was identified by following Bergey’s Manual of Determinative Bacteriology.They were belongs from genera Bacillus sp. and Panibacillus sp.